ALTERNATİF ÇATIYA GÖRE MANYETİK EĞRİLER - TAN, AHMET (Fırat Üniveristesi, 2024)
Öklid uzayında eğriler teorisinde farklı çatılara göre birçok çalışma yapılmıştır. Birçok bilim adamı bu teoride Frenet çatı, Bishop çatı, Adapted çatı, Ribbon çatı gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu çalışmada, 3-boyutlu Öklid uzayında Alternatif çatıya göre manyetik eğriler incelenmiştir. Öncelikle N-manyetik, C-manyetik ve W-manyetik eğrileri verilmiştir. Sonra alternatif çatıya göre bu eğrilerin Fermi-Walker türevleri araştırılmıştır.

Many studies have been done according to different frames of the theory of curves in Euclidean Space. Many scientists have studied frames such as Frenet frame, Bishop frame, Adapted frame, Ribbon Frame in this theory. These frames help us in the characterization of curves. In this study, magnetic curves according to Alternative frame in 3-dimensional Euclidean space are investigate firstley, N-magnetic, C-magnetic, W-magnetic, curves are givenThen the Fermi-Walker derivative of magnetic curves according to this frame are investigated.
Magnetic curves according to the alternative frame
Keywords: Matematik